Genetic variety of maize in China - Лі Цзінь; В. Л. Жемойда; А. К. Пархоменко; О. С. Макарчук (Plant Varieties Studying and Protection)
Main directions and results of Research on genetic diversity of maize in China and their practical use in breeding are represented.